Constraints on the number of X‐ray pulsars in IC 10 from a deep XMM‐Newton observation. Issue 1 (28th March 2019) - Yang, J.; Laycock, S. G. T.; Wik, D. R.
Abstract : We report the most sensitive search yet for X‐ray pulsars in the dwarf starburst galaxy IC 10, which is known to contain a population of young, high‐mass X‐ray binaries. We searched for pulsations in 207 point‐like X‐ray sources in the direction of IC 10 by a 2012 XMM‐Newton observation with a total exposure time of 134.5 ks. Pulsation searches in faint objects can be sensitive to the energy bands of the light curves, as well as the source and background extraction areas. We analyzed separately the PN and metal–oxide–semiconductor barycenter corrected 0.2–12 keV data, with good time interval filtering. Different schemes for source and background extraction were compared, and the search was repeated in the narrower 0.5–8 keV energy band to increase the signal‐to‐noise ratio. For the most conservative parameters, five point sources produced significant peaks in the Lomb–Scargle periodogram (99% significance, single trial, assuming white noise). A similar number of different candidates result from alternative analyses. A ∼4, 100 s period seen in all three instruments for the black hole (BH) + Wolf–Rayet binary IC 10 X‐1 is probably due to red noise of astrophysical origin. Considering the periods, luminosities, and spatial distribution of the pulsar candidates in the direction of IC 10, they do not belong to the same distribution as the ones in the Magellanic Clouds and Milky Way. This result holds even if the candidates are spurious, since if the Small Magellanic Cloud were placed at the distance of IC 10, we would expect to see nearly five pulsars at L x > 10 36 erg s –1 inside the D 25 contour, and their periods would be of order 100 s, rather than the mostly ∼1 s periods for the candidates reported here, which lie outside the main body of the galaxy.